Risk assessment and bioburden evaluation of Agrobacterium tumefaciens-mediated transient protein expression in plants using the CaMV35S promoter - Matthias Knödler; Paul Winman Reunious; Johannes Felix Buyel (BMC Biotechnology, 2023)
Abstract Large-scale transient expression of recombinant proteins in plants is increasingly used and requires the multi-liter cultivation of Agrobacterium tumefaciens transformed with an expression vector, which is often cloned in Escherichia coli first. Depending on the promoter, unintentional activity can occur in both bacteria, which could pose a safety risk to the environment and operators if the protein is toxic. To assess the risk associated with transient expression, we first tested expression vectors containing the CaMV35S promoter known to be active in plants and bacteria, along with controls to measure the accumulation of the corresponding recombinant proteins. We found that, in both bacteria, even the stable model protein DsRed accumulated at levels near the detection limit of the sandwich ELISA (3.8 µg L−1). Higher levels were detected in short cultivations (< 12 h) but never exceeded 10 µg L−1. We determined the abundance of A. tumefaciens throughout the process, including infiltration. We detected few bacteria in the clarified extract and found none after blanching. Finally, we combined protein accumulation and bacterial abundance data with the known effects of toxic proteins to estimate critical exposures for operators. We found that unintended toxin production in bacteria is negligible. Furthermore, the intravenous uptake of multiple milliliters of fermentation broth or infiltration suspension would be required to reach acute toxicity even when handling the most toxic products (LD50 ~ 1 ng kg−1). The unintentional uptake of such quantities is unlikely and we therefore regard transient expression as safe in terms of the bacterial handling procedure.